Metall i bunn og grunn. Metallutvinning i Oslo, ca 1150-1250 e. Kr. - Astrid Kristoffersen (Primitive Tider, 2018)
Summary. It has been doubted whether people in peripheral Norway were able to master the technique of extracting metal from solid rock, prior to the Late Middle Ages, when German miners prospected and explored ore deposits. This paper sheds light on metallurgists working in the medieval Old town of Oslo, their access to local raw materials, and their metallurgical expertise and abilities. It is argued that people living in Oslo had access to the rock mineral galena (PbS), and that by AD 1150–1200, at the latest, they had the technology to produce lead. It can be contended that metallurgical activities took place in two different areas of the town. The study also indicates that local lead was in circulation simultaneously as lead from foreign sources, which may have provided new opportunities for actors in the town. While the lead was used to produce so-called everyday products, indications of serial production of spinning whorls, exceeding that of a normal household, could have been connected to a specialized industry for shoe production. Furthermore, this paper demonstrates how with crossdisciplinary methods, new information can be gathered from old treasures.